42 How hard do we look for atrial fibrillation?. (5th June 2017) - Merinopoulos, Ioannis; Alam, Sajid; Bloore, David
Abstract : Brief introduction: Identifying atrial fibrillation (AF) after ischaemic stroke changes the recommendation from antiplatelets to anticoagulation. Currently, there is no clear consensus on the duration of rhythm monitoring post stroke. EMBRACE and CRYSTAL AF have shown that prolonged monitoring is superior to standard management in identifying AF. In our study, we aim to identify the percentage of patients who get referred for implantable loop recorder (ILR) by providing real-world data from The Ipswich Hospital. Methods: We identified all patients diagnosed with an ischaemic stroke (101) or TIA (71) to The Ipswich Hospital between 1st June 2015 and 31st August 2015. The medical records, hospital admission, follow-up records and investigations were reviewed. Results: Table 1 shows the patient characteristics of 101 patients with stroke and 71 patients with TIA. Figure 1 shows the investigations of stroke patients. All patients had an admission ECG. In 53 out of 71 patients in sinus rhythm on admission, identifying AF would change management. We excluded patients already anticoagulated for other reasons and patients who died or were deemed candidates for palliative care only. Out of those 53 patients, 39 (73.5%) had 24h tape, telemetry or pacemaker check and 7 (17.9%) had new AF. 13 patients (24.5%) did not have 24h tape. There was a tendency for patients with lacunar strokes not to get screened for AF. However, the detection rate of AF is similar between lacunar and non-lacunar strokes (fig 1). Figure 2 shows the investigations of TIA patients. All patients had an ECG. In 61 out of 63 patients in sinus rhythm, identifying AF would change management (2 patients were already anticoagulated). 41% of these patients did not have 24h tape. Conclusion: We did not identify any patients who got referred for ILR. We identified a significant proportion of patients with stroke or TIA who did not have 24 hour tape, 24.5% and 41% correspondingly. We would propose to consider an ILR in patients with ischaemic stroke or TIA who are<60 years old with normal ECG, 24 hour tape, US/MRA carotids especially if they have recurrent episodes or multiple territories are involved. If we apply these criteria, we would recommend 40 extra ILR implantations per year in our medium sized hospital. We also identified a tendency for patients with lacunar strokes not to get screened for AF even though the detection rate of AF is similar between lacunar and non-lacunar strokes. The relationship of lacunar strokes with AF is the subject of an ongoing debate in literature. However, the main focus of stroke management should be the identification of modifiable risk factors even when the mechanism of a particular stroke uncertain. As the most recent guidelines (ESC 2016) do not differentiate between ischaemic stroke subtypes when considering anticoagulation in patients with AF, then perhaps an equal effort should be made to identify AF in patients with lacunar and non-lacunar strokes.